Predictors of early growth failure in preterm, very low birth weight infants during hospitalization - Noviyani Leksomono; Retno Sutomo; Ekawaty Lutfia Haksari (Indonesian Pediatric Society, 2019)
Background Preterm, very low birth weight (VLBW) infants experience intrauterine nutritional deficits and perinatal comorbidities that may impair early growth parameters. Early growth failure has detrimental effects on later growth and neurodevelopment in childhood. Objective To analyze predictors of early growth failure in preterm, VLBW infants and differences in early growth parameters between small-for-gestational age (SGA) and appropriate-for-gestational age (AGA) infants. Methods This retrospective cohort study was conducted at Dr. Sardjito Hospital, Yogyakarta from 2011 to 2016. Subjects were preterm infants, with birth weights of 1,000-1,499 g. Twins, those who died during hospitalization, were discharged against medical advice, or had incomplete medical records were excluded. Adequate intrauterine growth was determined by the Lubchenco table criteria. Growth parameters and perinatal comorbidities were collected from medical records. Growth failure was defined as discharge weight less than 10th percentile of the Fenton growth curve. Bivariate and multivariate analysis were used to analyze potential predictive factors of early growth failure. Results Of 646 preterm, VLBW infants during the study period, 398 were excluded. Respiratory distress and SGA were predictors of early growth failure (AOR 6.94; 95%CI 2.93 to 16.42 and AOR 34.44; 95%CI 7.79 to 152.4, respectively). Mean weight velocities in SGA and AGA infants were not significantly different [16.5 (SD 5.9) and 17.5 (SD 5.3) g/kg/day, respectively; (P=0.25)]. Median time to regain, time to reach full feeding, and time to reach 120 kcal/kg/day were also not significantly different between SGA and AGA infants. Conclusions SGA and respiratory distress are predictors of early growth failure in preterm, VLBW infants during hospitalization. The SGA infants grow slower than AGA infants.